Gastrointestinal symptoms have a minor impact on autism spectrum disorder and associations with gut microbiota and short-chain fatty acids - Deng, Wenlin; Wang, Siqi; Li, Fang; Wang, Fang; Xing, Yi Pei; Li, Yongchun; Lv, Ying; Ke, Haoran; Li, Zitong; Lv, Pin Jing; Hao, Hu; Chen, Ye; et al. (Frontiers in Microbiology, 2022)
Children with autism spectrum disorder (ASD) experience gastrointestinal (GI) issues more frequently and severely than children who are typically developing (TD). The connections between gastrointestinal problems, microbiota, and short-chain fatty acids (SCFAs) in ASD are still being debated. We enrolled 90 children, 45 of whom were diagnosed with ASD, and examined the impact of GI disorders on ASD. The six-item GI Severity Index questionnaire was used to evaluate gastrointestinal symptoms, while the Social Responsiveness Scale was used to evaluate autism symptoms. Further, the Children's Sleep Habits Questionnaire and the Children's Eating Behavior Questionnaire are used to assess sleep and eating disorders in children. We assessed fecal microbiota by 16S rRNA gene sequencing, and SCFA concentrations by gas chromatography/mass spectrometry. The results revealed that children with ASD exhibited a high rate of gastrointestinal issues (78%), as well as higher rates of social impairment and poor sleeping habits, compared to TD children. However, GI disturbances have a minor impact on autism. In addition, the levels of propionic acid, butyric acid, and valeric acid were significantly higher in the ASD group. Besides, the ASD, TD, and GI subgroups possessed distinct microbiome profiles. These findings suggest that gastrointestinal disturbances have no discernible effect on the core symptoms of autism. Although autism may not cause an increase in GI symptoms directly, alterations in metabolites, such as SCFAs, may cause GI symptoms.